ANALISIS MOTIVASI PARA TENAGA PENDIDIK DENGAN STATUS HONORER - Anita Akhiruddin (Program Studi Manajemen Universitas Muhammadiyah Gresik, 2019)
Developing and forming dignified character for the nation's civilization in the framework of educating the nation's life, developing students to become human beings who believe and fear the Almighty God, character that is noble, healthy, knowledgeable, creative, capable, independent, and changing in search of the country democracy and responsibility is one of the functions of national education. To achieve these goals the education needs to be preceded by an adequate educational process. This research uses descriptive-qualitative paradigm approach. Data Collection Techniques Include: Interview Method, Observation or Observation Method and Documentation Method. research results Factor of pride and bonding of a teacher becomes stronger when, found many students from among the poor who can actually compete from students who come from upper middle class. Here will increase the spirit of teachers to serve even more strongly devote himself, although with a mediocre salary.